2016
DOI: 10.1080/02670836.2015.1119931
|View full text |Cite
|
Sign up to set email alerts
|

Very high cycle fatigue of bearing steels with artificial defects in vacuum

Abstract: At high-strength steels very high cycle fatigue (VHCF) failure always occurs at subsurface inclusions. As a result, the failure shows large scatter and is not observable or predictable prior to failure. In order to understand the mechanisms leading to crack initiation in VHCF, it is necessary to make the failure observable. Within our work, a new testing procedure is introduced that enables the simulation of subsurface conditions at the surface and thereby the localisation of the failure. Therefore, specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The characteristics of FGA in VHCF of high-strength steels have been reported in detail by several researchers. 34,35,38,46,47 However, for the VHCF of titanium alloys, the present paper is likely the first time to reveal the nature of nanograins in and only in the RA of fatigue crack initiation for the case of R = À1. The notch effect and the size effect on VHCF behavior for titanium alloys are also very important topics.…”
Section: It Is Shown Inmentioning
confidence: 85%
“…The characteristics of FGA in VHCF of high-strength steels have been reported in detail by several researchers. 34,35,38,46,47 However, for the VHCF of titanium alloys, the present paper is likely the first time to reveal the nature of nanograins in and only in the RA of fatigue crack initiation for the case of R = À1. The notch effect and the size effect on VHCF behavior for titanium alloys are also very important topics.…”
Section: It Is Shown Inmentioning
confidence: 85%
“…grain refinement) is caused by the interaction between the dislocations in the vicinity of crack origin or initiated crack tip due to local high stress [33]. The micro crack forms within the refined grains [29,34] due to the decrease of threshold value for crack initiation in regions of fine grains [35], or along the fine graincoarse grain interface. The first case would lead to the observation of fine grains in the mated fracture surfaces; and the second case would give rise to observation of fine grains only in one side of the fracture surface.…”
Section: Discussionmentioning
confidence: 99%
“…But surface failure is not known to lead to VHCF in high‐strength steels. For fatigue test with artificial surface defects, only if fatigue tests are performed in vacuum VHCF cracks initiate by FGA formation as shown by Spriestersbach et al In an air environment, no surface failure is observed for high‐strength steels in VHCF in these tests with surface defects. Thus, for high‐strength steels, the threshold for surface failure definitely would be questionable.…”
Section: Introductionmentioning
confidence: 89%